Blood, Nation, Science, and Language: Essentializing Race from the Sixteenth Century to the Present - Nancy P. Appelbaum (Latin American Research Review, 2020)
This essay reviews the following works: The Cultural Politics of Blood, 1500–1900. Edited by Kimberly Anne Coles, Ralph Bauer, Zita Nunes, and Carla L. Peterson. New York: Palgrave Macmillan, 2015. Pp. vii + 274. $95.00 hardcover. ISBN: 9781137338204.   Speaking of Spain: The Evolution of Race and Nation in the Hispanic World. By Antonio Feros. Cambridge, MA: Harvard University Press, 2017. Pp. ix + 370. $45.00 hardcover. ISBN: 9780674045514.   Theorizing Race in the Americas: Douglass, Sarmiento, Du Bois, and Vasconcelos. By Juliet Hooker. New York: Oxford University Press, 2017. Pp. ix + 280. $53.00 hardcover. ISBN: 9780190633691.   The Science and Politics of Race in Mexico and the United States, 1910–1950. By Karin Alejandra Rosemblatt. Chapel Hill: University of North Carolina Press, 2018. Pp xii + 255. $29.95 paperback. ISBN: 9781469636405.   Race and the Brazilian Body: Blackness, Whiteness, and Everyday Language in Rio de Janeiro. By Jennifer Roth-Gordon. Oakland, CA: University of California Press, 2017. Pp. ix + 248. $27.95 paperback. ISBN: 9780520293809.   Degrees of Mixture, Degrees of Freedom: Genomics, Multiculturalism, and Race in Latin America. By Peter Wade. Durham, NC: Duke University Press, 2017. Pp. vii + 344. $27.95 paperback. ISBN: 9780822363736.